2021
DOI: 10.1097/icb.0000000000000762
|View full text |Cite
|
Sign up to set email alerts
|

Combined Internal Limiting Membrane Flap and Autologous Plasma Concentrate to Close a Large Traumatic Macular Hole in a Pediatric Patient

Abstract: Summary Statement The authors describe a surgical technique using autologous plasma concentrate with internal limiting membrane flap to successfully close a large, traumatic macular hole in a pediatric patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…7,14,15 Many other techniques for macular hole closure have been described, including radial retinal incisions, autologous blood and platelet products, and inverted ILM flaps. [8][9][10] In our study, perimacular hole Tano brushing to oppose the edges of the macular hole in 1 child during the second operation resulted in successful anatomic closure. In another child, platelet-rich plasmin was used during the second vitrectomy, resulting in successful closure.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…7,14,15 Many other techniques for macular hole closure have been described, including radial retinal incisions, autologous blood and platelet products, and inverted ILM flaps. [8][9][10] In our study, perimacular hole Tano brushing to oppose the edges of the macular hole in 1 child during the second operation resulted in successful anatomic closure. In another child, platelet-rich plasmin was used during the second vitrectomy, resulting in successful closure.…”
Section: Discussionmentioning
confidence: 52%
“…The present study is the largest series to our knowledge of pediatric macular holes operated on with microincisional surgery, and corroborates a high single (81%) and final (94%) success rate that others have reported (67% to 100%) in smaller series. 1,2,8,10,11,13 The study cohort was similar to other studies in regard to preoperative duration. 4,5 Surgical techniques varied based on each surgeon's preference, but ILM peeling and internal tamponade were mostly uniformly pursued, as has been advocated for idiopathic macular holes.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Modifications such as the use of viscoelastic cap, perfluorocarbon liquid (PFCL), autologous blood clot, and cabbage-leaf technique have been proposed to prevent flap dislocation. [ 25 26 27 28 29 30 31 ]…”
Section: Discussionmentioning
confidence: 99%
“… 88 Recently, it was described a case in which inverted ILM flap assisted by autologous plasma concentrate was successfully performed in a pediatric patient with traumatic large FTMH. 97 A comparative study showed a closure rate of 92% and 75%, and VA improvement of 5 lines and 2.5 lines after inverted ILM flap and ILM peeling, respectively. 98 The authors concluded that the inverted ILM flap technique provides a better outcome in traumatic FTMHs than ILM peeling.…”
Section: Surgical Outcomes Of Inverted Ilm Flap Techniquementioning
confidence: 97%